191k views
1 vote
What is the solution to the system of equations -2x-y=1 -6x=3y+3

User Aventic
by
5.6k points

1 Answer

3 votes

2
x

y
=
1
;

6
x
=
3
y
+
3

Step: Solve

2
x

y
=
1
for y:

2
x

y
=
1

2
x

y
+
2
x
=
1
+
2
x
(Add 2x to both sides)

y
=
2
x
+
1

y

1
=
2
x
+
1

1
(Divide both sides by -1)
y
=

2
x

1

Step: Substitute

2
x

1
for
y
in

6
x
=
3
y
+
3
:

6
x
=
3
y
+
3

6
x
=
3
(

2
x

1
)
+
3

6
x
=

6
x
(Simplify both sides of the equation)

6
x
+
6
x
=

6
x
+
6
x
(Add 6x to both sides)
0
=
0

Answer:
Infinitely many solutions.
User Usman Rana
by
4.9k points